Grain discoloration in different genotypes of durum wheat (Triticum durum L.) in Argentina: associated mycobiota and peroxidase activity - Cipollone, María Josefina (2020)
Wheat grain discoloration, a worldwide disease that lowers grain quality and decreases grain yield, does not have a single etiology. It has been proposed that it is a consequence of an abiotic mechanism, a response to environmental conditions or enzymatic activity. It has also been suggest that it is a biotic mechanism, a fungal infection principally by Alternaria spp. and Bipolaris sorokiniana. The present work was carried out to analyze the possible etiology of this disease in nine durum wheat genotypes from two localities of southern Buenos Aires province (Argentina) on two sowing dates. Incidence (percentage of grain discoloration) was recorded and mycobiota associated with this pathology was registered following ISTA rules. Peroxidase activity in an extract obtained from grains belonging to genotypes of the locality that showed the highest incidence was measured. The incidence among genotypes, localities and sowing dates varied, although the genotypes with the higher and lower values of incidence were the same for all the variables tested. The fungus Alternaria spp. was isolated the most frequently followed by Fusarium spp., while Bipolaris sorokiniana was found the least frequently. Peroxidase activity showed that all the treatments had similar levels of enzymatic activity, but there was no clear differentiation between controls either between genotypes with the lowest or the highest incidence values. This suggests that peroxidase activity did not have a clear relationship with grain discoloration. In this research, it is presumed that fungal infection is the main cause of this disease.